2020
DOI: 10.1007/s00701-020-04536-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral nitric oxide and mitochondrial function in patients suffering aneurysmal subarachnoid hemorrhage—a translational approach

Abstract: Background Cerebral ischemia and neuroinflammation following aneurysmal subarachnoid hemorrhage (SAH) are major contributors to poor neurological outcome. Our study set out to investigate in an exploratory approach the interaction between NO and energy metabolism following SAH as both hypoxia and inflammation are known to affect nitric oxide (NO) metabolism and NO in turn affects mitochondria. Methods In seven patients under continuous multimodality neuromonitoring suffering poor-grade aneurysmal SAH, cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Correlation between brain NO, glutamate levels and clinical outcome in SAH patients. In our previous studies, we have shown an increase in NO metabolites in preclinical model of acute traumatic brain injury [ 9 ] and in patients during the acute phase of SAH [ 10 ]. In the current study we explore the pathophysiological consequences of these observations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Correlation between brain NO, glutamate levels and clinical outcome in SAH patients. In our previous studies, we have shown an increase in NO metabolites in preclinical model of acute traumatic brain injury [ 9 ] and in patients during the acute phase of SAH [ 10 ]. In the current study we explore the pathophysiological consequences of these observations.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work [ 10 ] has demonstrated a positive correlation between glutamate and NO metabolites in the brain. Combined with the current data this lead us to an assumption that elevated NO levels impair glutamate metabolism and that elevated glutamate levels were associated with the negative clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, mitochondrial dynamics and mitophagy are critical for maintaining cellular function and homeostasis [ 62 , 63 ]. Abundance of evidence has revealed the occurrence of mitochondrial dysfunction after SAH, which was found to be associated with EBI and neurological outcome [ 64 - 68 ]. The relationship between mitochondria and EBI after SAH needs to be further established.…”
Section: Mitochondria and Ebi After Sahmentioning
confidence: 99%